Four Famous Dans of Peking Opera —An Analysis of the Sound Forms in the Performance of Zhang Junqiu and His Inheritors (Journal of Global Arts Studies, 2024)
Background: Zhang Junqiu is a famous performer of Peking Opera dan roles in China, with a beautiful, elegant, and relaxed voice. The two important inheritors of Zhang Junqiu's singing art, Zhao Xiujun and Wang Runjing, also have different voices in their performances. Objective: To analyze the vocal forms of the three singers in order to objectively understand their voices. Methods: The study adopted the research method of music acoustics and used the method of sound measurement. Results: Firstly, in terms of pitch. Zhang Junqiu's singing tone is higher than that of Zhao Xiujun and Wang Runjing. Secondly, in terms of timing. The performances of Zhao Xiujun and Wang Runjing are generally longer and slower than those of Zhang Junqiu. Thirdly, in terms of volume. Zhao Xiujun sang with a loud volume, much larger than Zhang Junqiu and Wang Runjing. Wang Runjing is slightly louder than Zhang Junqiu, but the difference is small. Fourthly, in terms of timbre. The tones of the three are all round, full, and bright. Wang Runjing has the most rounded, full, and bright tone among the three, with Zhao Xiujun in the middle and Zhang Junqiu at the end. Conclusion: Zhang Junqiu's singing voice is beautiful, relaxed, and elegant, with a unique charm. Zhao Xiujun, the inheritor, sang with a bright, full, loud volume, and slightly resonant voice. The voice of inheritor Wang Runjing during her singing is full, slightly louder, and resonates strongly. From the perspective of inheriting the singing art of Zhang Junqiu's Dan role, inheritors should not deliberately "display" their vocal conditions and technical abilities during singing.
Keywords: Zhang Junqiu; Zhao Xiujun; Wang Runjing; Sound form